Improving the technology of gluten-free bread from composite flour mixtures - A. I. Soloveva; D. A. Bragina; Yu. V. Ushakova; G. Y. Rysmukhambetova (Новые технологии, 2024)
The article presents the research on the development of bread technology from gluten-free composite mixtures: No. 1 from a mixture of rice and flax flour (70: 30), No. 2 from flax and corn flour (50: 50) and No. 3 from pumpkin and corn flour (50: 50). A sociological survey conducted has shown that potential consumers are interested in expanding the line of gluten-free food products in the Saratov region. The following technological parameters for the production of gluten-free bread were determined: proofing time – 100 minutes, chamber temperature 35°С and relative air humidity 40%. The bread was baked for 9 minutes at 200°С and 35 minutes at 180°С with a relative humidity in the working chamber of 40%. Physicochemical studies showed that the moisture content in three samples of gluten-free bread was 1.17 times higher than the norm (46.0) compared to the control. In turn, the acidity of the sample crumb was in the range of 5.5–7.2 degrees, respectively, which exceeded the norm. The crumb porosity of the developed samples was 65.22–68.03%, respectively, while less than 68% was explained by the use of gluten-free mixtures, which were unable to form an elastic elastic frame in the products. The developed gluten-free bread contained QMAFAnM, coliform bacteria, Staphylococcus aureus, bacteria of the genus Proteus, mold fungi and pathogenic microorganisms, including Salmonella, and complies with TR CU 021/2011.As a result of the research, sample No. 3 was selected from pumpkin and corn flour (50: 50), which had high performance in terms of overall physicochemical and organoleptic characteristics. The selected sample had dimensional stability, pleasant taste, aroma and baked crumb.